Heroin Smuggling in Serbia - Radović, Nenad (Kriminologijos studijos, 2018)
[full article, abstract in English; abstract in Lithuanian] Drug trafficking is a very lucrative criminal activity, with a growing number of organized criminal groups from the Balkans. According to Europol’s report, about 5000 organized criminal groups are active in the European Union.2 According to the results of the National survey on the lifestyles of the citizens in the Republic of Serbia in 2014, the use of psychoactive substances and games of chance and illegal drug use at least once during a lifetime was recorded at 8.0% of the total population aged 18 to 64 (10.8% of males and 5.2% of females), with greater prevalence (12.8%) in the younger adult population aged 18 to 34. The number of heroin users who inject drugs in Serbia is between 10 000 and 25 000. The main estimated number is 20 000 heroin users who inject drugs, i.e., 0.4% of the population aged 15 to 64. Based on the analysis of data on drug-related deaths, it can be noted that there has been a decline in the number of deaths in the past five years, and most of these cases are related to opiates. In the territory of the Republic of Serbia, the production of heroin has not been recorded, and that gives trafficking a greater primacy, which is supported by the fact that high quality heroin is further trafficked in the form of a base that is mixed with other substances (paracetamol, caffeine, sugar etc.). In this way, such a high degree of purity of heroin allows the members of criminal groups to increase the quantity of narcotics by mixing substances suitable for this and, in that way, achieve greater profits. The most commonly used illegal drug among the adult population is cannabis (marijuana and hashish), and the use of the mentioned drugs has been recorded at least once during a lifetime in 7.7% of subjects aged 18 to 64 (10.4% of men and 4.9% of women). The use of other illegal drugs is very rare; 1.6% of questioned individuals (2.5% of the population aged 18 to 34) have used other illegal drugs.